Strategi Pengelolaan Hubungan Industrial Perusahaan Dalam Upaya Menerapkan Revolusi Industri 4.0 Agar Tidak Terjadi Konflik Antara Pengusaha dan Pekerja - Bintang Satrio Febtiyansyah; Muhamad Rizal; Sari Usih Natari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The fourth industrial revolution is defined as the application of technology, intelligent systems, and automation to industrial operations. In this case the 4.0 revolution is an industrial revolution which is a general transformation phase in the industrial world related to data exchange and automation in factory technology, robotic technology and artificial intelligence. With the 4.0 industrial revolution, many things have changed in various sectors, where in the operational activities of a company it does not require many workers to run it, because it has been replaced by the use of technological machines. Thus, many workers will be laid off because they are replaced by technology. In order to implement the industrial revolution 4.0, this study aims to provide a solution by identifying a suitable company industrial relations management strategy. This way, there won't be any conflicts between employers and employees, and businesses can implement the industrial revolution 4.0 without running afoul of the workforce. A qualitative technique was employed in this study throughout the stages of data collection employing library research to gather various books, journals, or other online sources that are relevant to the issues and study objectives. Then the data obtained is then identified using the descriptive method so that general conclusions can be drawn relating to the company's industrial relations management strategy which is suitable in the effort to implement the industrial revolution 4.0 so that there is no conflict between employers and workers.